Antibiotic Reversal Activity of Piper longum Fruit Extracts against Staphylococcus aureus Multi-Drug Resistant Phenotype - Ud Din, Maryam Salah; Gohar, Umar Farooq; Mukhtar, Hamid; Khan, Ibrar; Morris, John; Pornpukdeewattana, Soisuda; Massa, Salvatore (My University, 2023)
Irrational and injudicious use of antibiotics, easy availability of them as over-the-counter drugs in economically developing countries, and unavailability of regulatory policies governing antimicrobial use in agriculture, animals, and humans, has led to the development of multi-drug resistance (MDR) bacteria. The use of medicinal plants can be considered as an alternative, with a consequent impact on microbial resistance. We tested extracts of Piper longum fruits as new natural products as agents for reversing the resistance to antibiotics. Six crude extracts of P. longum fruits were utilized against a clinical isolate of multidrug-resistant Staphylococcus aureus.The antibiotic susceptibility testing disc method was used in the antibiotic resistance reversal analysis. Apart from cefoxitin and erythromycin, all other antibiotics used (lincosamides [clindamycin], quinolones [levofloxacin and ciprofloxacin], and aminoglycosides [amikacin and gentamicin]) were enhanced by P. longum extracts. The extracts that showed the greatest synergy with the antibiotics were EAPL (ethyl acetate [extract of] P. longum), n-BPL (n-butanol [extract of] P. longum), and MPL (methanolic [extract of] P. longum The results of this study suggest that P. longum extracts have the ability to increase the effectiveness of different classes of antibiotics and reverse their resistance. However, future studies are needed to elucidate the molecular mechanisms behind the synergy between antibiotic and phytocompound(s) and identify the active biomolecules of P. longum responsible for the synergy in S. aureus.
Keywords: antibiotic resistance reversal; antibiotics; Piper longum; plant extracts